Case Report: Multiple colorectal cancers in a patient with Ulcerative colitis and Lynch syndrome: Is there a role for prophylactic colectomy? A short report and review of literature - Ayeni, Adewale Adeoba; Waterland, Peter; Evans, Matthew; Singhal, Shika; Patel, Rajan Kumar; Akingboye, Akinfemi (Frontiers in Oncology, 2022)
It is a known fact that Lynch syndrome (LS) and Ulcerative colitis (UC) are individually associated with increased risk of colorectal cancer. While there is no conclusive evidence to demonstrate a cumulative risk when these two conditions coexist, available data suggest early onset and synchronous cancers are synonymous to this group. We have reported an unusual case of multiple synchronous colorectal cancers in a young man with ulcerative colitis and Lynch syndrome also known as Hereditary Nonpolyposis Colorectal Cancer (HNPCC) gene mutation. We propose that conducting a detailed genetic mutation profile in LS patients may play a key role in guiding the intensity of endoscopic surveillance and that a concerted, pragmatic, patient guided approach should be adopted on the subject of prophylactic colectomy when UC and LS co-exist.